The role of nutritional and inflammatory markers in predicting postoperative complications after esophagectomy for esophageal squamous cell carcinoma: mechanisms, clinical applications, and future perspectives - Shi, Junjie; Tang, Sujie; Shen, Cheng; Xu, Dafu; Tian, Wen Ze; Xu, Zhiyun (Frontiers in Surgery, 2025)
Esophageal squamous cell carcinoma (ESCC) is a prevalent malignancy with a high mortality rate, for which esophagectomy remains the cornerstone of curative treatment. However, this complex surgical procedure is associated with significant postoperative morbidity and mortality. Nutritional status and systemic inflammatory response are critically intertwined and play a pivotal role in the host's ability to withstand surgical stress and mount an effective recovery. This review aims to provide a comprehensive overview of the role of nutritional and inflammatory markers in predicting postoperative complications following esophagectomy for ESCC. We first elucidate the intricate biological mechanisms through which malnutrition and systemic inflammation compromise tissue repair, immune function, and overall surgical outcomes. We then systematically evaluate the predictive value of various individual markers, such as albumin, C-reactive protein (CRP), and neutrophil-to-lymphocyte ratio (NLR), as well as combined scoring systems like the Prognostic Nutritional Index (PNI) and the Glasgow Prognostic Score (GPS). The clinical application of these markers in preoperative risk stratification, guiding perioperative immunonutrition, and dynamic monitoring for early complication detection is thoroughly discussed. Finally, we highlight future perspectives, including the integration of novel biomarkers from metabolomics and proteomics, the application of artificial intelligence in building sophisticated prediction models, and the design of marker-guided precision intervention trials. A deeper understanding and smarter utilization of these readily available and cost-effective markers will pave the way for personalized perioperative management, ultimately improving the prognosis for patients with ESCC undergoing esophagectomy.